Edmund Burke's Irish identities (Irish Acad. Press, 2007)
Edmund Burke was an orator, writer, British statesman, and opponent of the revolution in France. This collection of essays focuses on Burke's complex relationship to his native Ireland. It brings together 13 authors, all established experts and young scholars, from a variety of viewpoints and disciplines.